A smartphone-assisted high-throughput integrated color-sensing platform for the rapid detection of Campylobacter coli. (15th September 2022) - Lin, Qijie; Jia, Kaiyuan; Gou, Hongchao; He, Haishan; Wen, Junping; Shen, Haiyan; Chen, Kaifeng; Wu, Yuqian; Lu, Bijia; Liao, Ming; Han, Yuxing; Zhang, Jianmin
Abstract: Campylobacter is one of the most common foodborne pathogens worldwide. A new smartphone-assisted high-throughput integrated color-sensing platform, called the HICS platform, was developed for the rapid detection of Campylobacter coli . This platform was based on the visual loop-mediated isothermal amplification method. Using this system, as many as 64 samples could be assessed in less than an hour after enrichment. 60 meat samples were tested to compare the performance of the HICS platform and other methods. Having the consistent detection result with TaqMan qPCR (Quantitative Real-time Polymerase Chain Reaction), the HICS platform was able to reliably detect C. coli in meat samples, and its limit of detection is 550 CFU/mL and 120 copies/μL, which was 10-fold higher than that of the PCR (Polymerase Chain Reaction) method. To conclude, considering that our platform showed robust performance and does not require any expensive equipment, it can also be reliably applied for the high-throughput detection of other pathogens. Graphical abstract: Image 1 Highlights: A high-throughput color-sensing platform was developed to detect Campylobacter coli . A colorimetric LAMP method was developed for rapid and sensitive detection of Campylobacter coli . A 3D-printed cassette was fabricated for a stable data visualization environment. Hue-saturation-intensity color space was used for hue analyses of sample images. A smartphone was used for data visualization, and images were stored in the cloud.